2017
DOI: 10.2139/ssrn.3040075
|View full text |Cite
|
Sign up to set email alerts
|

Auctions and Leaks: A Theoretical and Experimental Investigation

Abstract: We study first-and second-price private value auctions with sequential bidding where second movers may discover the first movers bids. There is a unique equilibrium in the first-price auction and multiple equilibria in the second-price auction. Consequently, comparative statics across price rules are equivocal. We experimentally find that in the first-price auction, leaks benefit second movers but harm first movers and sellers. Low to medium probabilities of leak eliminate the usual revenue dominance of first-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…See alsoFischer et al (2014), who found that first-price auctions do not generate higher seller revenue compared to second-price auctions if there is a non-negligible probability that one bidder's bid leaks to the other bidder.…”
mentioning
confidence: 99%
“…See alsoFischer et al (2014), who found that first-price auctions do not generate higher seller revenue compared to second-price auctions if there is a non-negligible probability that one bidder's bid leaks to the other bidder.…”
mentioning
confidence: 99%